Operations and control of unmanned underwater vehicles - Márcio Correia (2005)
Operations and control of unmanned underwater vehicle systems are discussed in terms of systems and technologies, vehicles, operational deployments and concepts of operation. The notions underlying the specification of single vehicle operations are contrasted to new concepts of operation to illustrate the challenges they pose to control engineering. New research directions are discussed in the context of the theories and techniques from dynamic optimization and computer science. The overall discussion is done in the context of the activities of the Underwater Systems and Technology Laboratory from Porto University.